The effect of nitrogen fertilisation on the yield and quality of winter wheat grain on meadow‐chestnut soil - S. A. Teymurov; M.‐R. A. Kaziev; A. A. Bagomaev (Юг России: экология, развитие, 2023)
Aim. The study of the effect of nitrogen fertilization on the yield and quality of winter wheat grain on meadow‐chestnut soil.Methods. Analyses of soil samples were carried out using generally accepted standard techniques. Assessment of the biological yield of grain and its structure was carried out according to the "Methodology of the State Variety Testing of Agricultural Crops". Tillage for winter crops after stubble predecessors was carried out according to the irrigation halfsteam system.Results. With an increase in the hydrothermal coefficient, a more elastic gluten is formed. Studies have shown that as the dose of nitrogen fertilizing increases, the indicators of the sowing qualities of seeds and the baking qualities of winter wheat grain of the Grom variety improve. In the best variant N90P90, the following indicators were obtained: seed germination energy – 99%, germination – 100%, weight of 1000 grains – 34.7 g, protein content – 14.8%, gluten 27.4%, which represent respectively 4%; 4%; 3.9 g; 1.3% and 6.1% more than in the control variant without the use of mineral fertilizers and higher than in the variants N30P90 and N60P90.Conclusion. The research area determines the use of the high‐intensity Thunder variety, which helps to stabilise productivity and improve product quality. The use of nitrogen top dressing (N30, N60 and N90) against the background of P90 increases the yield of winter wheat grain from 6.25 to 7.90 t / ha and improves the main indicators of baking qualities of grain: protein – 14.3–14.8% and gluten – 22.1–27.4%, the best option with nitrogen top dressing being a dose of N90 (N30 in autumn + N60 in spring).